2008
DOI: 10.1002/jemt.20564
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian collagen IV

Abstract: Four decades have passed since the first discovery of collagen IV by Kefalides in 1966. Since then collagen IV has been investigated extensively by a large number of research laboratories around the world. Advances in molecular genetics have resulted in identification of six evolutionary related mammalian genes encoding six different polypeptide chains of collagen IV. The genes are differentially expressed during the embryonic development, providing different tissues with specific collagen IV networks each hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
504
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(519 citation statements)
references
References 177 publications
5
504
0
10
Order By: Relevance
“…The chains interact and assemble with specificity to form three distinct patterns: a1a1a2, a3a4a5 and a5a5a6. 11 The a5-and a6-chains are found in the basement membrane of skin, smooth muscle and kidney. 12 Two transcripts of COL4A6 are known, isoforms A and B (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…The chains interact and assemble with specificity to form three distinct patterns: a1a1a2, a3a4a5 and a5a5a6. 11 The a5-and a6-chains are found in the basement membrane of skin, smooth muscle and kidney. 12 Two transcripts of COL4A6 are known, isoforms A and B (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…Using IHC analysis, we found variable IGF-IR levels in clinical specimens of hepatic metastases that did not always correlate with collagen IV levels (data not shown). Although the regulation of collagen IV gene expression is not yet fully understood (Khoshnoodi et al, 2008), several factors have been identified, including high glucose levels, transforming growth factor-b1 (Iglesias-de la Cruz et al, 2002), hypoxia via the hypoxia-inducible factor (HIF)-1a (Steenhard et al, 2010) and the tumor-suppressor von Hippel-Lindau that in addition to its role in regulating HIF-1a levels was also implicated in the assembly of collagen IV matrix (Kurban et al, 2008). Some of these factors have also been shown to play important roles during the early stages of liver metastasis (VidalVanaclocha, 2008).…”
Section: Lung Metastasismentioning
confidence: 99%
“…The C-terminal NC1 domain is important in the initiation of triple helix formation. [23][24][25] Mice harboring heterozygous mutations in Col4a1 or Col4a2 suffer from hemorrhage in the eye, brain, and skin, which already occur during gestation and sometimes lead to developmental defects of the eye and brain. Therefore, similarities in phenotypes between COL4A1 and COL4A2 mutations were to be expected.…”
Section: Introductionmentioning
confidence: 99%